A study to assess the effectiveness of self-instructional module on minor ailments of children among anganwadi workers - Jamra, Vishal; Mahore, Ramniwas; Saxena, Dinesh Mohan; Agarwal, Anil Kumar (International Journal Of Community Medicine And Public Health, 2017)
Background: Anganwadi workers (AWW) are India’s primary tool against the menace of child malnourishment, infant mortality, and lack of child education, community health. The Anganwadi workers should have basic knowledge of treatment of minor ailment in under five children. Methods: This cross sectional study was conducted on 48 AWWs of selected ICDS centers of District Bhopal, Madhya Pradesh by simple random sampling method. Results: Brief structured interview and structured questionnaire techniques were used to collect responses from the AWWs. All the AWWs (48) were trained and had been rendering adequate services but they were not much reflective of the same when being questioned on the knowledge parameter. The study revealed that out of 48 AWW, more than 80% were in the age group of 25-45 years. After IMCI based training given to AWWs, their knowledge and skills for treating minor ailments under five children was significantly improved from pre-test assessment (Total score 1087 with Mean (SD) score 2.83 (1.32) to post-test assessment1392 with Mean (SD) score 3.62 (1.38). Knowledge of AWWs regarding under five children in all 8 domains of illness was changed significantly 14.1% from 50.3% in baseline survey to 64.4% in end line survey. Conclusions: As the Anganwadi worker is the key person in the programme, her education level and knowledge of minor ailments for under five children plays an important role related to her performance in the Anganwadi centre.